Modelling the innovation-decision process for hydrogen homes: an integrated model of consumer acceptance and adoption intention - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Haq, Anwar Ul; Nabavi, Seyed Ali (Elsevier, 2024)
As the global energy transition progresses, a range of drivers and barriers will continue to shape consumer attitudes and behavioural intentions towards emerging low-carbon technologies. The innovation-decision process for technologies composing the residential sector such as hydrogen-fuelled heating and cooking appliances is inherently governed by the complex interplay between perceptual, cognitive, and emotional factors. In response, this study responds to the call for an integrated research perspective to advance theoretical and empirical insights on consumer engagement in the domestic hydrogen transition. Drawing on online survey data collected in the United Kingdom, where a policy decision on ‘hydrogen homes’ is set for 2026, this study systematically explores whether an integrated modelling approach supports higher levels of explanatory and predictive power. Leveraging the foundations of the unified theory of domestic hydrogen acceptance, the analysis suggests that production perceptions, public trust, perceived relative advantage, safety perceptions, knowledge and awareness, and positive emotions will shape consumer support for hydrogen homes. Conversely, perceived disruptive impacts, perceived socio-economic costs, financial perceptions, and negative emotions may impede the domestic hydrogen transition. Consumer acceptance stands to significantly shape deployment prospects for hydrogen boilers and hobs, which are perceived to be somewhat advantageous to natural gas appliances from a technological and safety perspective. The study attests to the predictive benefits of adopting an integrated theoretical perspective when modelling the early stages of the innovation-decision process, while acknowledging opportunities for leveraging innovative research approaches in the future. As national hydrogen economies gain traction, adopting a neuroscience-based approach may help deepen scientific understanding regarding the neural, psychological, and emotional signatures shaping consumer perspectives towards hydrogen homes.
Keywords: Energy transitions; Green hydrogen production; Hydrogen homes; Importance-performance map analysis; Predictive modelling; Unified theory of technology acceptance; 40 Engineering; 34 Chemical Sciences; Basic Behavioral and Social Science; Behavioral and Social Science; 7 Affordable and Clean Energy; Energy